THE USE OF TOTAL PHYSICAL RESPONSE METHOD ON THE STUDENTS’ LEARNING MOTIVATION - Wahyuningsih, Yulia; Maretha, Carla; Alrajafi, Gali (Universitas Muhammadiyah Lampung, 2023)
This paper reported on the findings of Total Physical Response (TPR) method on the students’ learning motivation. This study belongs to an experimental research. The subjects of this study were the students of Universitas Muhammadiyah Lampung at the first semester in academic year 2022/2023. The writer uses questionnaire to know the students’ responses toward using the TPR method in the classroom. Then the researcher masured the students’ motivation by questionnaire test and analyzed the data by using T-test formula. The findings showed that there was a significant influence on using the Total Physical Response method toward the students’ learning motivation.